NUMERICAL ANALYSIS OF A VERTICAL HELICAL EARTH-AIR HEAT EXCHANGER - Vaz, I. S.; Griebeler, S.; Rodrigues, M. K.; Rocha, L. A. O.; dos Santos, E. D.; Isoldi, L. A. (Revista de Engenharia Térmica, 2023)
The Earth-Air Heat Exchanger (EAHE) is an equipment that consists of ducts buried in the ground in which the air is forced to pass through. The heat exchange with the surrounding soil turns the air temperature in the outlet section of the EAHE milder. Due to that, the EAHE is capable of assist air conditioning systems and reduce energy consumption, by taking advantage of the temperature gradient established between the soil surface and its layers. In the current study, the operation of Vertical Helical EAHEs was numerically evaluated with different distances between helicoid curves, for the city of Viamão, located in the southern Brazil. The results stated that the Vertical Helical EAHE with dimensions between the curves equivalent to 100 and 200 mm presented the better thermal performances for cooling mode operation in the hottest seasons of the years, when compared to the Conventional Horizontal EAHE adopted as reference. Frim this comparison, the obtained average values of the Root Mean Squared Error (RMSE) were, respectively, 0.47 °C and 0.66 °C. At last, it must be highlighted a sevenfold reduction in the soil volume occupied by the installation of the Helical EAHE compared to the Conventional Horizontal EAHE.